2011
DOI: 10.1128/aac.01351-10
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Platelet Chemokine Antimicrobial Activity: Nuclear Magnetic Resonance Backbone Dynamics of NAP-2 and TC-1

Abstract: The platelet chemokines neutrophil-activating peptide-2 (NAP-2) and thrombocidin-1 (TC-1) differ by only two amino acids at their carboxy-terminal ends. Nevertheless, they display a significant difference in their direct antimicrobial activities, with the longer NAP-2 being inactive and TC-1 being active. In an attempt to rationalize this difference in activity, we studied the structure and the dynamics of both proteins by nuclear magnetic resonance (NMR) spectroscopy. Using 15 N isotope-labeled protein, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 65 publications
(80 reference statements)
3
23
0
Order By: Relevance
“…Comparison of our data to the previously reported relaxation data of CXCL7 in the presence of chloroethanol shows striking differences for the 30s-loop residues. Heteronuclear NOE measurements in the presence of 2-chloroethanol indicate a highly dynamic 30s-loop, especially residues Q33, V34 and E35, showing very low NOE values observed for the very terminal residues, whereas our values are similar to those of structured residues [16,31,32]. These observations suggest that chloroethanol influences dynamic properties, and so, these data may not fully reflect the dynamics of the native protein.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Comparison of our data to the previously reported relaxation data of CXCL7 in the presence of chloroethanol shows striking differences for the 30s-loop residues. Heteronuclear NOE measurements in the presence of 2-chloroethanol indicate a highly dynamic 30s-loop, especially residues Q33, V34 and E35, showing very low NOE values observed for the very terminal residues, whereas our values are similar to those of structured residues [16,31,32]. These observations suggest that chloroethanol influences dynamic properties, and so, these data may not fully reflect the dynamics of the native protein.…”
Section: Resultsmentioning
confidence: 63%
“…Our structure showed a backbone RMSD of 0.82 Å compared to the monomer units of the tetramer over the same regions, and differences in these regions are mainly due to extended β-strands and a slight change in the orientation of the helix. The largest differences between our monomer and the tetramer structure were observed for the N-terminus and 30s-loop residues, which can be attributed to their conformational flexibility [16,31,32] (Figure 3A). In general, we observed that the more dynamic a region, the greater the difference in its backbone RMSD.…”
Section: Resultsmentioning
confidence: 98%
“…This truncation is required for strong antimicrobial activity (2), but it does not substantially affect chemokine activity (39). In NAP-2, the negatively charged C terminus folds back over the positively charged surface and may thus interfere with antimicrobial activity (40). The C-terminal truncation generating TC-1 reduces the negative charge of the C terminus and thus abolishes interference of the C terminus with the positive patch (40).…”
Section: Discussionmentioning
confidence: 99%
“…(D) Electrostatic surface diagram showing the extension of the positive patch created through TC-1 dimerization. Panels (B) and (D) reprinted with permission from Nguyen et al (2011b). …”
Section: Chemokine-derived Antimicrobial Fragmentsmentioning
confidence: 99%
“…The last four residues of NAP-2 were not included in the X-ray crystal structure due to poorly defined electron density in this region (Malkowski et al, 1995). NMR relaxation experiments reveal that, although the last five residues are overall quite flexible compared to the rest of NAP-2, the final two residues become more motionally restricted than the residues immediately preceding them (Figure 2B) (Nguyen et al, 2011b). By comparison, the TC-1 backbone continually increases in flexibility toward the end of its sequence and the C-terminus was not seen to fold back over the α-helix in the corresponding peptide.…”
Section: Structural Determinants For Antimicrobial Activitymentioning
confidence: 99%